Web-based protected geoinformation system of criminal analysis (RICAS) for analytical support for crimes investigation - Uzlov, D. J.; Узлов, Д. Ю.; ORCID: http://orcid.org/0000-0003-3308-424X; Strukov, V. M.; Струков, В. М.; ORCID: http://orcid.org/0000-0003-4722-3159 (4th International Scientific-Practical Conference Problems of Infocommunications. Science and Technology (PIC S&T`2017) (Kharkiv, Ukraine, 10-13 oct. 2017). - Kharkiv, 2017. - P. 508-511, 2017)
У роботі розглянута проблема застосування веб-орієнтованих геоінформаційних інструментаріїв для підвищення ефективності інформаційно-аналітичної роботи в органах внутрішніх справ. Виконано огляд зарубіжних аналогів. В якості вирішення запропонована розроблена веб-орієнтована захищена геоінформаційна система кримінального аналізу - RICAS для аналітичного супроводу розслідування злочинів. Описано її призначення, функціональні можливості, особливості реалізації, переваги в порівнянні з існуючими аналогами та новизна.

This article is devoted to the problem of appliance of web-oriented geoinformation tools for improving the effectiveness of information-analitical work in the internal affairs. It has gone the overview of foreign automated information and analytical works. As a solution to the problems set forth proposed to use developed web-oriented protected geoinformation system of criminal analysis – RICAS for analytical support of crimes investigation. Its purpose, functionality, implementation features, benefits compared with existing analogues and novelty are described.

В работе рассмотрена проблема применения веб-ориентированных геоинформационных инструментариев для повышения эффективности информационно-аналитической работы в органах внутренних дел. Выполнен обзор зарубежных аналогов. В качестве решения предложена разработанная веб-ориентированная защищенная геоинформационная система криминального анализа – RICAS для аналитического сопровождения расследования преступлений. Описаны её назначение, функциональные возможности, особенности реализации, преимущества по сравнению с существующими аналогами и новизна.
Веб-ориентированная защищенная геоинформацион-ная система криминального анализа (RICAS) для аналитического сопровождения расследования преступлений
Uzlov, D. Web-based protected geoinformation system of criminal analysis (RICAS) for analytical support for crimes investigation / Dmytro Uzlov, Volodymyr Strukov // 4th International Scientific-Practical Conference Problems of Infocommunications. Science and Technology (PIC S&T`2017) (Kharkiv, Ukraine, 10-13 oct. 2017). - Kharkiv, 2017. - P. 508-511.
Keywords: geoinformation system; crime analysis; implicit connection; hidden patterns; unified display space; visual analysis; Наукові публікації. Scientific publications. Научные публикации; геоінформаційна система; кримінальний аналіз; неявні зв'язки; приховані закономірності; єдиний простір відображення; візуальний аналіз; геоинформационная система; криминальный анализ; неявные связи; скрытые закономерности; единое пространство отображения; визуальный анализ; RICAS; publikatsii u WoS